Perancangan Produk Fashion Anak Menggunakan Metode SCAMPER untuk Inovasi Desain Local Brand Sugacoat Studios - Bastaman, Widia Nur Utami; Anatha, Dava Dien; Febriani, Rima; Larissa, Tiara (Serat Rupa: Journal of Design, 2024)
Bandung is one of the cities known to have an excellent creative industry ecosystem, one of which is due to the rapid growth of local brands. As we know, local brands grow by relying on consistent creativity and innovation. One of Bandung's local brands currently on the rise is Sugacoat Studios, which focuses on developing bag and hat accessories products for children. The rapid development of local brands in Bandung requires Sugacoat Studios to continue innovating to develop new products. However, the process of creating innovation is challenging. One of the crucial stages is the process of designing the product. So far, Sugacoat Studios has applied a commonly used design method to design products based on specific concepts and mood board. However, this often makes design deadlocks, ultimately making the resulting product design less than optimal. This research will present the product design process by applying the SCAMPER method that the Sugacoat Studios brand has never applied. The SCAMPER design method, which stands for Substitute, Combine, Adapt, Modify, Put into Another Use, Eliminate, and Reverse, has previously been successfully applied to the fashion product design process. Applying the SCAMPER design method is expected to give Sugacoat Studios a new strategy in the product design process that will be more structured, thus helping to create product innovation. Applying this design method strategy will also be aligned with the brand character so that the resulting design will still represent the brand character well. The output of this research is a product design that has applied the SCAMPER design method.